2009
DOI: 10.1080/14786410802168494
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity from polar and non-polar extracts of some Chenopodiaceae wild species growing in Tunisia

Abstract: Nine plants belonging to Chenopodiaceae family were collected around salt marshes near Monastir, located in the east Mediterranean coast of Tunisia. They were tested for their antifungal activities against six plant pathogenic fungi: Botrytis cinerea, Fusarium oxysporum f. sp. niveum, F. solani f. sp. cucurbitae, Phytophthora cactorum, Rhizoctonia solani and Nattrassia mangiferae. Data of this study showed that the highest inhibition of Botrytis cinerea growth was observed with the petroleum ether extract of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…Also known as Mediterranean saltbush, Atriplex halimus L. is a euhalophyte native in the broad Mediterranean region usually used as a fodder or for medicinal purposes (Walker et al, 2014). According to Boughalleb et al (2009) and Bendaly et al (2016), low to moderate salinity had a stimulating effect on plant growth mainly due to promoting root and stem growth, while the salt tolerance could be attributed to compartmentalization of high amounts of Na + , the 2016a Total phenolic content is expressed as gallic acid (GAE) equivalents (mg gallic acid g −1 dry weight (DW)). b Total phenolic compounds as determined by LC-DAD-ESI/MS.…”
Section: Botanical Aspectsmentioning
confidence: 99%
“…Also known as Mediterranean saltbush, Atriplex halimus L. is a euhalophyte native in the broad Mediterranean region usually used as a fodder or for medicinal purposes (Walker et al, 2014). According to Boughalleb et al (2009) and Bendaly et al (2016), low to moderate salinity had a stimulating effect on plant growth mainly due to promoting root and stem growth, while the salt tolerance could be attributed to compartmentalization of high amounts of Na + , the 2016a Total phenolic content is expressed as gallic acid (GAE) equivalents (mg gallic acid g −1 dry weight (DW)). b Total phenolic compounds as determined by LC-DAD-ESI/MS.…”
Section: Botanical Aspectsmentioning
confidence: 99%
“…In addition, several water and methanol extracts of the 16 cultivars selected from Taiwanese indigenous wild bitter gourd ( Momordica charantia ) showed inhibitory activity against the growth of E. coli and Salmonella enterica [116]. Results of another study revealed that a petroleum ether extract of wild Atriplex inflata fruits possessed high inhibitory activity against Botrytis cinerea [117]. …”
Section: Bioactivities Of Wild Fruitsmentioning
confidence: 99%
“…Recently, triterpenoids isolated from A. laciniata demonstrated antibacterial, antioxidant and antiurease activities ( 15 ), including anticholinesterase effects against Alzheimer's and other neurological disorders ( 16 ). The fungicidal effects of A. semibaccata, A. portulacoides and A. infalata have been previously reported ( 17 ) and the molluscicidal and larvicidal activities of A. inflata have also been identified ( 18 ). Furthermore, Gođevac et al ( 19 ) revealed that flavonoid glycosides isolated from the aerial parts of A. littoralis exhibited protection against in vitro biochemical and cytogenetic damage to human lymphocytes ( 19 ).…”
Section: Introductionmentioning
confidence: 96%